The Financial Accounting Standards Towards Small Middle Enterprise to The Financial Statement - Fachruddin, Wan; Arnita, Vina; Sari, Andini Puspita (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The Micro, Small and Medium Enterprises (MSMEs) play a pivotal role in driving Indonesia's economy due to their ability to adapt to rapid market changes, an advantage that large corporations lack. Supporting MSMEs is vital to ensure their sustainable growth, while opening up more business and employment opportunities. This research adopted a qualitative approach and was conducted in Pari City, focusing on MSMEs as the research subjects. Data were collected through observations, interviews, and documentation, then analyzed using reduction, presentation, and conclusion techniques. Despite this, Kota Pari's Gula Merah MSMEs still face obstacles in financial management, especially related to the unavailability of financial reports in accordance with standards. Financial management is also still inadequate, with the lack of accounting recording practices, indicating a lack of understanding of the importance of systematization in financial recording and reporting. Although efforts have been made to monitor trade receivables, there is no record of cash disbursements, potentially resulting in a lack of control over business cash flow. Based on the existing financial statements, it can be concluded that the financial statements of Pari City MSMEs do not fully comply with the Micro and Small Financial Accounting Standards (SAK EMKM), still relying on the cash basis. Further efforts are needed to improve the financial management of MSMEs to ensure better business sustainability and growth.